ESTIMATION OF AGE BASED ON THE STAGES OF ERUPTION OF PERMANENT 2nd AND 3rd MOLAR TEETH. (Indian Internet Journal of Forensic Medicine and Toxicology, 2003)
A community based study on the time of eruption of permanent 2nd and 3rd molar teeth to establish the age of an Individual was  undertaken on 1100 subjects (550 males and 550 females) residing in Delhi, in the age group of 10-21 yrs. Correlation between the age and eruption time of individual tooth was calculated stage wise in both jaws. Eruption time of each tooth was to vary not only from population to population but also with in the same population. This is why the present study was undertaken in view of this because there is a significant time lag between the cutting of the tooth in to the oral cavity and completion of eruption (i.e. completion of bite), and hence it was felt that in age determination cases, their actual age of eruption should be taken in to account.
Keywords: Age estimation; stages of eruption; permanent molars